Effects of Continuous Ingestion of Herbal Teas on Intestinal CYP3A in the Rat - Kazuhiro Matsuda; Yuki Nishimura; Norimitsu Kurata; Mariko Iwase; Hajime Yasuhara (Elsevier, 2007)
Tenryocha, rooibos, and guava teas are widely consumed as herbal beverages, especially as a therapy against pollen allergy. To investigate the possible herbal tea-drug interaction the effect of continuous ingestion of these teas on cytochrome P450 (CYP) 3A were studied. Rats (n = 6) were allowed free access to either tea (experimental groups) or water (control) for two weeks. Midazolam (MDZ) (20 mg/kg) was orally administered and the serum concentration was determined. The area under the serum concentration-time curve (AUC0-∞) and the maximum serum concentrations (Cmax) of MDZ were reduced by more than 60% after the treatment of tenryocha and rooibos tea (P<0.05). Intestinal MDZ 1'- and 4-hydroxylation activities mediated by CYP3A were increased in tenryocha and rooibos tea-treated group by 50% compared to the control group, although the results were not statistically significant. Furthermore, the Western blot analysis showed that CYP3A content was significantly increased in the intestine after the treatment of these teas (P<0.05). Hepatic MDZ hydroxylation and CYP3A content were slightly increased by these teas. The results suggested that two weeks ingestion of tenryocha and rooibos tea reduced serum concentration of MDZ by the induction of intestinal CYP3A. The possible interaction between tenryocha or rooibos tea and medicines mediated by CYP3A was suggested. Keywords:: CYP3A, herbal tea, herb-drug interaction, tenryocha, rooibos